2022
DOI: 10.3390/ph15020131
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Statins on Prostate Cancer Patients Receiving Androgen Deprivation Therapy or Definitive Therapy: A Systematic Review and Meta-Analysis

Abstract: Mortality associated with statin use has been reported in prostate cancer (PCa) patients treated with androgen deprivation therapy (ADT) or definitive therapy in several observational studies, although the results have varied. This study aimed to analyze the association of statin use with all-cause mortality and cancer-specific mortality among PCa patients receiving ADT or definitive therapy as their primary treatment and to examine the effect of statin initiation (pre-ADT) timing on outcomes. A systematic lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…In patients with prostate cancer who receive ADT as their primary treatment, the use of statins in conjunction with ADT has been shown to significantly reduce both all-cause mortality and cancer-specific mortality [ 27 ]. Prolonged use of ADT can lead to metabolic changes that may increase the risk of cardiovascular events [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with prostate cancer who receive ADT as their primary treatment, the use of statins in conjunction with ADT has been shown to significantly reduce both all-cause mortality and cancer-specific mortality [ 27 ]. Prolonged use of ADT can lead to metabolic changes that may increase the risk of cardiovascular events [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three recent meta-analyses have shown statins to be associated with improved overall survival in prostate cancer patients treated with ADT 13 , 21 , 27 . Two of those studies also found statins to be linked with better prostate cancer-specific survival 13 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Three recent meta-analyses have shown statins to be associated with improved overall survival in prostate cancer patients treated with ADT 13 , 21 , 27 . Two of those studies also found statins to be linked with better prostate cancer-specific survival 13 , 21 . Especially, the statin use after initiation of ADT has provided most consistent results showing statins to improve prognosis in patients with advanced PCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the combination of statins and radical prostatectomy improved cancer-specific mortality. However, the authors admitted that differences in the time, dose, and duration of statin treatment caused heterogeneity, and the most effective type of statin was not established [183].…”
Section: Clinical Evidence Of the Antitumoral Effects Of Statinsmentioning
confidence: 99%